Glass ceramic as well as preparation method and application thereof

By using sodium aluminum silicon crystallized glass to replace lithium aluminum silicate crystallized glass, adjust the components and heat treatment conditions to form crystallized glass with multiple crystallized glass, the problem of high production costs in the existing technology is solved, and the cost reduction and Improve the effect of mechanical properties.

CN119118516APending Publication Date: 2024-12-13深圳市昊迦科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411243404.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The production cost of existing high-strength transparent microcrystalline glass covers is relatively high, and the production cost of lithium-aluminosilicate microcrystalline glass is relatively high, which requires the reduction of production costs.

Method used

Sodium-aluminum-silicon crystallized glass is used to replace lithium-aluminum silicate crystallized glass. By adjusting different types of nucleation agents and their content, a microcrystalline glass formula containing one or more crystals is designed, including SiO2, Al2O3, Components such as Na2O, Li2O, K2O, MgO, ZrO2, B2O3, P2O5, T iO2 and SnO2, NaC l, Sb2O3 are heat treated to form a variety of crystals to reduce the amount of lithium use.

Benefits of technology

This reduces production costs, and at the same time, a variety of crystals can be precipitated from the formed microcrystalline glass, which improves its mechanical properties and impact resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118516A_ABST
    Figure CN119118516A_ABST
Patent Text Reader

Abstract

The invention discloses a glass ceramic and a preparation method and application thereof, and the glass ceramic comprises the following components by mole percent: 40-60% of SiO2; a: 10%-22% of l2O3; 12% to 25% of Na2O; 1%-9% of Li2O; 0%-1% of K2O; 0 to 4% of MgO; 0%-4% of CaO; 1% to 5% of ZrO2; 0.5% to 8% of B2O3; 0.5% to 5% of P2O5; 0%-3% of TiO2; and 0.1% to 2% of one or more of SnO2, NaCl and Sb2O3 in total. Wherein (Al2O3 + Na2O) / SiO2 is greater than or equal to 0.7 and less than or equal to 1.2, Li2O + Na2O is greater than or equal to 13% and less than or equal to 30%, and ZrO2 + P2O5 + TiO2 is greater than or equal to 1.5% and less than or equal to 8%. According to the present invention, the sodium aluminum silicon microcrystalline glass is adopted to replace the existing lithium aluminum silicate microcrystalline glass, such that the lithium use amount is reduced so as to reduce the production cost, and a variety of crystals can be precipitated from the microcrystalline glass formed by the formula so as to provide the good mechanical property and the good impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microcrystalline glass preparation, and in particular to microcrystalline glass and a preparation method and application thereof. Background Art

[0002] Glass-ceramics, also known as glass ceramics, is different from ordinary ceramics or glass in that it not only has the characteristic properties of glass, but also has some characteristics of ceramics, with dual advantages. In the process of studying glass-ceramics, high-strength transparent glass-ceramics cover is one of the main directions.

[0003] At present, the high-strength cover glass on the market is mainly lithium aluminum silicate glass-ceramics, but the production cost of lithium aluminum silicate glass-ceramics is relatively high.

[0004] Therefore, the prior art needs to be further improved and enhanced. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a microcrystalline glass and a preparation method and application thereof, aiming to reduce the production cost of the existing transparent microcrystalline glass cover.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0007] In a first aspect, a glass-ceramic comprises the following components in mole percentage:

[0008] SiO2: 40%~60%;

[0009] Al2O3: 10%~22%;

[0010] Na2O: 12%~25%;

[0011] Li2O: 1%~9%;

[0012] K2O: 0%~1%;

[0013] MgO: 0~4%;

[0014] CaO: 0%~4%;

[0015] ZrO2: 1%~5%;

[0016] B2O3: 0.5%~8%;

[0017] P2O5: 0.5%~5%;

[0018] TiO2: 0%~3%;

[0019] and one or more of SnO2, NaCl, Sb2O3 in a total amount of 0.1% to 2%;

[0020] Among them, 0.7≤(Al2O3+Na2O) / SiO2≤1.2, 13%≤Li2O+Na2O≤30%, 1.5%≤ZrO2+P2O5+TiO2≤8%.

[0021] In a second aspect, a glass-ceramic, wherein the glass-ceramic comprises the following components in mole percentage:

[0022] SiO2: 40%~60%;

[0023] Al2O3: 10%~22%;

[0024] Na2O: 12%~25%;

[0025] Li2O: 1%~7%;

[0026] K2O: 0%~1%;

[0027] MgO: 0.5~4%;

[0028] ZrO2: 1%~3%;

[0029] B2O3: 0.5%~5%;

[0030] CaO: 0%~4%;

[0031] P2O5: 0.5%~5%;

[0032] TiO2: 0~2%;

[0033] and one or more of SnO2, NaCl, Sb2O3 in a total amount of 0.1% to 2%;

[0034] Among them, 0.7≤(Al2O3+Na2O) / SiO2≤1.2, 13%≤L i2O+Na2O+K2O≤30%, 1.5%≤ZrO2+P2O5+T i O2≤8%, 0.5%≤CaO+MgO+K2O≤8%.

[0035] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0036] As a preferred technical solution, the microcrystalline glass, wherein the crystal phase of the microcrystalline glass includes: one or more of sodium nepheline, nepheline solid solution, triclinic nepheline, zirconium oxide, sodium phosphate, sodium silicate, and β-quartz solid solution.

[0037] As a preferred technical solution, the microcrystalline glass has a total crystallinity of more than 20% and less than 80%.

[0038] As a preferred technical solution, the microcrystalline glass, wherein the DSC curve of the base glass corresponding to the microcrystalline glass has a single crystallization peak or a double crystallization peak, and the intensity of the weak peak in the double crystallization peak is 5% to 80% of the strong peak.

[0039] As a preferred technical solution, in the microcrystalline glass, the microcrystalline glass phase with the weak peak in front in the double crystallization peak is mainly triclinic nepheline, and the microcrystalline glass phase with the strong peak in front is mainly sodium nepheline.

[0040] As a preferred technical solution, the microcrystalline glass has an average crystal size greater than 5 nm and less than or equal to 60 nm.

[0041] As a preferred technical solution, the microcrystalline glass, wherein, at a thickness of 0.7 mm, has a transmittance greater than 89.00% at a wavelength of 400 to 750 nm.

[0042] In a third aspect, a method for preparing the above-mentioned microcrystalline glass comprises:

[0043] Weigh the components according to the proportion, mix, melt and shape the components to obtain the basic glass; wherein the melting temperature is 1450-1700°C;

[0044] The basic glass is subjected to a first heat treatment and a second heat treatment in sequence to obtain the microcrystalline glass; the first heat treatment temperature is 350-600°C, and the second heat treatment temperature is 540-1100°C.

[0045] In a fourth aspect, an electronic device comprises: a frame and glass arranged at an opening of the frame, wherein the material of the glass is the microcrystalline glass as described in any one of the above items.

[0046] Beneficial effects: Compared with the prior art, the present invention uses sodium aluminum silicate glass-ceramics to replace the existing lithium aluminum silicate glass-ceramics, thereby reducing the use of lithium and thus reducing production costs. At the same time, since a variety of crystals can be precipitated in the glass-ceramics formed by this formula, it has good mechanical properties and impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 A DSC curve diagram of the base glass provided in an embodiment of the present invention with a weak peak in front and a strong peak in the back;

[0048] Figure 2A DSC curve diagram of a base glass provided in an embodiment of the present invention, wherein a strong peak is preceded by a weak strong peak;

[0049] Figure 3 A crystal phase spectrum of triclinic nepheline provided in an embodiment of the present invention;

[0050] Figure 4 The crystalline phase spectrum of sodium nepheline provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0051] The present invention provides a glass-ceramic and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0052] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementation methods. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and do not mean a necessary sequence, unless otherwise specified that a certain sequence must be followed. The serial numbers themselves, such as "first", "second", etc., assigned to the components herein are only used to distinguish the objects described and do not have any order or technical meaning.

[0053] Terminology explanation:

[0054] Basic glass: glass obtained by uniformly mixing compounds containing the oxides, melting and casting at high temperature, or rolling or drawing, and then annealing without undergoing nucleation, crystallization, heat treatment, or ion exchange strengthening treatment.

[0055] Glass-ceramics: also known as microcrystalline glass, is a type of solid composite material that contains both glass phase and crystal phase (microcrystalline phase, crystalline phase) and is prepared by subjecting base glass to a targeted controlled crystallization heat treatment.

[0056] Nucleation: The base glass is heat treated to make the nucleating material in the glass grow tiny crystal nuclei.

[0057] Crystallization: The base glass is heat treated to grow a certain crystal based on the crystal nucleus.

[0058] Crystalline phase: Crystalline phase is the microscopic structure of crystals, which is a general term for parts composed of a large number of crystalline solid phases.

[0059] In the embodiment of the present invention, the transmittance of the microcrystalline glass at a wavelength of 400-1000nm or 550nm is the average transmittance of multiple glass samples of the same batch measured at a wavelength of 400-1000nm or 550nm. At least 5 samples of each batch of microcrystalline glass are taken for testing.

[0060] Instruments and test methods

[0061] Glass thickness: Determined by micrometer test. The thickness change of glass-ceramics before and after chemical strengthening is very small and can be ignored.

[0062] Crystallinity: The percentage of nanocrystalline components in the entire microcrystalline glass volume, which is also expressed as the crystal content. The test method is: use an X-ray diffractometer to test the microcrystalline glass sample to obtain the XRD diffraction peak curve, and then import the X-ray diffractometer (Rigaku SmartLab 3kw) test result file (RAW format) into the X-ray diffraction data Rietveld refinement software (such as Gsas, Full prof, Maud), perform fitting and calculation, and the crystal content in the microcrystalline glass sample can be obtained. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content. The X-ray diffractometer used in the present invention is Rigaku SmartLab 3kw, the diffraction angle range used for the test is 2θ=10~80°, the scanning speed is 10° / min, the working voltage is 40KV, and the working current is 30mA.

[0063] The method for obtaining the average grain size is: using an X-ray diffractometer to test the microcrystalline glass sample, and using the Scherrer formula D = Kλ / (βcosθ) for the result data obtained from the XRD test, where λ is the X-ray wavelength, β is the peak half-height width, and K = 0.89, the average grain size can be obtained.

[0064] Transmittance test: According to the standard of GB / T 7962.12-2010 Test method for colorless optical glass Part 12: Spectral transmittance, the transmittance of microcrystalline glass is tested using professional testing instruments. The testing instruments used in the present invention are Konica Minolta CM-3600A and Shimadzu UV-visible spectrophotometer UV-2600.

[0065] Haze: The cloudy or turbid appearance of the interior or surface of a transparent or translucent material due to light diffusion, expressed as the percentage of the diffused luminous flux to the luminous flux transmitted through the material. Haze is the percentage of the scattered luminous flux Td of a part of the parallel light that deviates from the incident direction by more than 2.5° due to scattering inside and on the surface of the material when a beam of parallel light from a standard "c" light source is vertically irradiated onto a transparent or translucent film, sheet, or plate to be transmitted through the material. It is an important parameter for the optical transparency of transparent or translucent materials.

[0066] Color control LAB value: Lab values ​​represent the brightness, red-green color, and yellow-cyan color of a color. The larger the L value, the higher the brightness of the color. When a>0, it means the color is red, and the larger the a value, the redder the color. When a<0, it means the color belongs to the green system. b>0 is yellow, and b<0 is cyan. Color parameters: L value (Lightness), between 0 and 100, 0 is black, 100 is white: a value (Redness), represents the color between red and green, 100 is red, ~80 is green; b value (Yellowness), represents the color between yellow and blue, 100 is yellow, ~80 is blue.

[0067] The present invention adopts the following method to test the physical and chemical properties of glass-ceramics:

[0068] (1) Using a PerkinElmer Lambda UV-visible spectrophotometer, test the transmittance (i.e., visible light transmittance) in the wavelength range of 400nm to 750nm in accordance with GB / T40415 standard;

[0069] (2) The crystal phase composition of glass-ceramics can be analyzed by Rigaku Smart l ab X-ray diffraction (XRD) testing; the crystal phase composition, crystallinity, and the proportion of each crystal phase can be analyzed by JADE.

[0070] (3) Synchronous thermal analysis test: Netzsch STA 449F3 synchronous thermal analyzer is used to perform the test according to the required process. The obtained temperature rise curve is called DSC curve.

[0071] (4) Testing method of DSC curve: Break the base glass into particles, select about 10 mg of sample, place it in a platinum crucible, and heat it from room temperature to 1400°C at a heating rate of 5°C / min under a nitrogen atmosphere. Use the instrument's built-in software to analyze and measure the exothermic peak of the curve.

[0072] It can be understood that the above-mentioned testing methods and testing equipment are commonly used methods for evaluating the relevant properties of microcrystalline glass in the industry. They are only a means to characterize or evaluate the technical scheme and technical effects of the present invention. Other testing methods and testing equipment may also be used without affecting the final results.

[0073] The microcrystalline glass of the present invention is designed according to the Na2O-Al2O3-SiO2 ternary phase diagram, and based on the sodium aluminum silicate system, different types of nucleating agents and their contents are adjusted to finally obtain microcrystalline glass containing one or more crystals.

[0074] Specifically, the microcrystalline glass includes the following components, in molar percentage: SiO2: 40% to 60%; Al2O3: 10% to 22%; Na2O: 12% to 25%; Li2O: 1% to 9%; K2O: 0% to 1%; MgO: 0% to 4%; CaO: 0% to 4%; ZrO2: 1% to 5%; B2O3: 0.5% to 8%; P2O5: 0.5% to 5%; TiO2: 0% to 3%; and one or more of SnO2, NaCl, and Sb2O3 totaling 0.1% to 2%; wherein 0.7≤(Al2O3+Na2O) / SiO2≤1.2, 13%≤Li2O+Na2O≤30%, and 1.5%≤ZrO2+P2O5+TiO2≤8%.

[0075] Among them, silicon dioxide (SiO2) is the basic component of microcrystalline glass. It is used to stabilize the glass structure, in which Si atoms and O atoms are bonded in the glass network to form the basic structural unit of the glass network, the [SiO4] tetrahedron. Each [SiO4] tetrahedron unit is connected by vertices, and the three-dimensional space expands to form a basic glass network. Theoretically, the higher the SiO2 content in the glass, the more stable the glass network and the better the various properties of the glass. However, if the SiO2 content is too high, the glass melting temperature will increase, increasing the process cost and energy consumption. In addition, SiO2 is also one of the components that form the nepheline crystal phase. Too little SiO2 addition will reduce the formation of nepheline and affect the haze of the glass product. In the microcrystalline glass component, the molar percentage of SiO2 is 40% to 60%, including but not limited to 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, and 60%.

[0076] Alumina (Al2O3) in microcrystalline glass can capture non-bridging oxygen to form [AlO4]. Nepheline belongs to a hexagonal crystal frame structure, and half of the [SiO4] in its structural grid is replaced by [AlO4]. Because the volume of [AlO4] is larger than that of [SiO4], the structure of the nepheline crystal is squeezed and tends to be compact. The addition of Al2O3 can also improve the chemical stability, thermal stability, mechanical strength and other properties of microcrystalline glass. In the microcrystalline glass component, the molar percentage of Al2O3 is 10% to 22%, including but not less than 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%.

[0077] Sodium oxide (Na2O) is a network outer body in glass-ceramics. + The ions are filled in the gaps of the structural grid and become relatively stable due to being squeezed. In addition, Na2O can reduce the melting temperature of the base glass and can also be used to control the viscosity of the glass during the crystallization process. However, too high a content of Na2O will reduce the chemical stability of the glass and may also cause the three-dimensional skeleton structure of the crystal to wrap around the residual glass phase, hindering the exchange of large ions in the molten salt to a deeper level. In the microcrystalline glass component, the molar percentage of Na2O is 12% to 25%, including but not limited to 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, and 25%.

[0078] Li2O can promote the melting of glass and reduce the melting temperature of glass. It is also the main component that replaces sodium ions during chemical strengthening, and can increase the surface stress of microcrystalline glass products. On the other hand, if too much Li2O is contained, it is easy to reduce the chemical stability of glass and the light transmittance of microcrystalline glass and microcrystalline glass products. Therefore, the addition amount of Li2O in the present invention is 1 to 9 mol%, including but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%.

[0079] Potassium oxide (K2O) is an optional component that helps improve the low temperature melting and formability of glass, but if too much K2O is contained, it is easy to reduce the chemical stability of the glass. Therefore, the molar percentage of K2O added is 0% to 1%, including but not limited to 0% and 1%.

[0080] MgO can improve the melting of glass, reduce the liquidus temperature, and have a good effect on improving the thermal stability of glass. At the same time, MgO improves the chemical stability and mechanical strength of glass, and can reduce the crystallization tendency of glass. However, when its content is high, the crystallization performance of glass is reduced, which is not conducive to obtaining the desired crystal phase type and grain size of microcrystalline glass. Therefore, the molar percentage of MgO in the microcrystalline glass component is 0% to 4%, including but not limited to 0%, 1%, 2%, 3%, and 4%.

[0081] CaO is a network modifier oxide, which is used to reduce the glass melting temperature and provide free oxygen to make aluminum oxide form aluminum-oxygen tetrahedron to supplement the glass network; CaO also plays a role in reducing the high-temperature viscosity of the glass liquid. The molar percentage of CaO in the microcrystalline glass component is 0% to 4%, including but not limited to 0%, 1%, 2%, 3%, and 4%.

[0082] The nucleation effect of zirconium oxide (ZrO2) in glass-ceramics is generally believed to be that zirconium-containing crystals are first precipitated from the parent phase, and then induce the parent glass to nucleate. ZrO2 can increase the hardness of glass-ceramics and improve the weather resistance and stability of glass, but too much ZrO2 will greatly increase the melting temperature of glass. The molar percentage of ZrO2 in the glass-ceramics component is 1% to 5%, including but not limited to 1%, 2%, 3%, 4%, and 5%.

[0083] B2O3 can improve the network structure of glass. If its content is too high, it is not conducive to glass molding, and it is easy to crystallize during molding, and the chemical stability is reduced. Therefore, the content of B2O3 is 0.5-8%, including but not limited to 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%.

[0084] Phosphorus oxide (P2O5) has good nucleation ability for silicate glass. It is generally believed that the reason why P2O5 promotes the nucleation of glass is that it can promote phase separation, reduce interfacial energy, and reduce nuclear activation energy. Phosphorus pentoxide (P2O5) is one of the commonly used raw materials in glass manufacturing. It is mainly used to reduce the alkali metal content in the glass component, improve the corrosion resistance and heat resistance of the glass, and increase the hardness and density of the glass. The glass transition temperature and crystallization temperature can also be controlled by adjusting the content of P2O5. The molar percentage of P2O5 in the microcrystalline glass component is 0.5% to 5%, including but not limited to 0.5%, 1%, 2%, 3%, 4%, and 5%.

[0085] Titanium oxide (TiO2) is usually used as a glass nucleating agent in nepheline glass-ceramics to promote glass nucleation. However, excessive TiO2 (e.g., 5% to 10%) will make the glass appear yellow or amber. Therefore, the amount of TiO2 added is 0% to 3%, including but not limited to 0, 1%, 2%, and 3%.

[0086] When melting the base glass, it is also necessary to add some clarifiers to facilitate homogenization of the glass components and eliminate internal bubbles. The clarifier includes at least one of SnO2, NaCl, and Sb2O3. The molar percentage of the clarifier in the microcrystalline glass component is 0.1% to 2%, including but not limited to 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, and 2.0%.

[0087] In some embodiments, the ratio of the total content of Al2O3 and Na2O to the content of SiO2 (Al2O3+Na2O) / SiO2 is controlled within the range of 0.7 to 1.1, and the ratio of (Al2O3+Na2O) / SiO2 is controlled within this range to better obtain the target crystal form. In some embodiments, the value of (Al2O3+Na2O) / SiO2 can be 0.7, 0.8, 0.9, 1.0, 1.1.

[0088] In some embodiments, the total content of Li2O and Na2O is controlled within the range of 16% to 30% to obtain the target crystal form. In some embodiments, the value of Li2O+Na2O may be 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%.

[0089] In some embodiments, the total content of ZrO2, P2O5 and TiO2 is controlled within the range of 2% to 8% to regulate crystallization. If it is too low, the crystallization ability is poor; if it is too high, other crystals may be formed, or excessive crystallization may cause devitrification, affecting optical properties. In some embodiments, the value of ZrO2+P2O5+TiO2 can be 2%, 3%, 4%, 5%, 6%, 7%, 8%.

[0090] In some embodiments, the total content of CaO, MgO and K2O is controlled within the range of 0.5% to 8% to reduce the melting point of the material, and does not affect the growth of other crystals while forming a network structure. In some embodiments, the value of CaO+MgO+K2O can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%.

[0091] In one embodiment, the components of the microcrystalline glass include, in molar percentage, SiO2: 40% to 60%; Al2O3: 10% to 22%; Na2O: 12% to 25%; Li2O: 1% to 7%; K2O: 0% to 1%; MgO: 0.5% to 4%; ZrO2: 1% to 3%; B2O3: 0.5% to 5%; CaO: 0% to 4%; P2O5: 0.5% to 5%; TiO2: 0% to 2%; the sum of the molar percentages of the components is 100%. Among them, 0.7≤(Al2O3+Na2O) / SiO2≤1.2, 13%≤Li2O+Na2O+K2O≤30%, 1.5%≤ZrO2+P2O5+TiO2≤8%, 0.5%≤CaO+MgO+K2O≤8%.

[0092] In one embodiment, multiple crystals are precipitated in the microcrystalline glass, including one or more of sodium nepheline, nepheline solid solution, triclinic nepheline, zirconium oxide, and sodium phosphate. When multiple crystals are precipitated, the interweaving of several crystals will increase the strength of the microcrystalline glass, similar to an interlocking structure. At the same time, the microcrystalline glass can also have good optical properties.

[0093] In one embodiment, the DSC curve of the base glass corresponding to the microcrystalline glass has a single crystallization peak or a double crystallization peak, the intensity of the weak peak in the double crystallization peak is 5% to 80% of the strong peak, and the microcrystalline glass phase with the weak peak in front is mainly triclinic pyroxene, while the microcrystalline glass phase with the strong peak in front is mainly sodium pyroxene.

[0094] In one embodiment, the total crystallinity of the microcrystalline glass is greater than 20% and less than 80%. The average crystal size is greater than 5 nm and less than or equal to 60 nm.

[0095] In one of the embodiments, when the glass-ceramics has a thickness of 0.70 mm, the transmittance of the glass-ceramics at a wavelength of 400 to 750 nm is greater than 89.00%.

[0096] The change of heat treatment temperature makes the crystals of the microcrystalline glass different. For example, when the crystallization temperature is in the range of 540-740°C during heat treatment, one or more of zirconium dioxide crystals, triclinic nepheline crystals or sodium nepheline crystals are precipitated; when the crystallization temperature is between 750-1100°C, one or both of sodium nepheline crystals and triclinic nepheline crystals are precipitated.

[0097] Based on the same inventive concept, the present invention also provides a method for preparing the microcrystalline glass, comprising the following steps:

[0098] S10, weighing raw materials according to the components, heating to 1450° C. to 1650° C., and keeping the temperature for 2 to 5 hours to prepare a molten liquid;

[0099] S20, pouring the molten liquid into a mold for molding, wherein the molding method includes but is not limited to float molding, drawing method, rolling method, and casting method, and annealing the molded glass at a temperature of 300 to 600° C. for 2 to 6 hours to obtain a basic glass;

[0100] S30, heat-treating the base glass at a temperature of 400° C. to 950° C. for 2 to 10 hours to prepare the microcrystalline glass.

[0101] The heat treatment step in step S30 includes a first heat treatment step and a second heat treatment step. The first heat treatment step is: keeping the temperature at 400°C to 590°C for 2 to 8 hours; the second heat treatment step is: heat treatment at 590°C to 950°C for 0.25 to 2 hours.

[0102] The processed microcrystalline glass is placed in molten salt for strengthening to obtain strengthened microcrystalline glass.

[0103] The above-mentioned microcrystalline glass is cut into glass sheets with a thickness of 0.7 mm to 0.8 mm, and then ground and polished.

[0104] It should be noted that the molding method is not limited, and in the case of a large output, it can be any one of the float method, overflow method, down-draw method, etc. The method provided in the examples of the present invention is only an example and is not limited to this method.

[0105] Based on the same inventive concept, the present invention further provides a glass device, which is prepared from the above-mentioned glass-ceramics. The glass device of the present invention can be regular or irregular. Those skilled in the art can manufacture it according to needs.

[0106] Based on the same inventive concept, the present invention also provides an electronic device, the electronic device of the present invention includes but is not limited to at least one of a mobile phone, a display (such as a car display, an aircraft display, etc.), a tablet computer, an electronic watch, a smart wearable (such as a smart bracelet, a smart watch, smart glasses), and a television. The glass material components used in the electronic device, such as the panel and the back panel, are all prepared by using the above-mentioned microcrystalline glass.

[0107] The above technical solution provided by the present invention is further explained below through specific embodiments.

[0108] Examples 1 to 8 were implemented according to the components and processes in the following table:

[0109]

[0110]

[0111] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A glass-ceramic, characterized in that: In terms of molar percentage, the microcrystalline glass comprises the following components: SiO2: 40%~60%; Al2O3: 10%~22%; Na2O: 12%~25%; Li2O: 1%~9%; K2O: 0%~1%; MgO: 0~4%; CaO: 0%~4%; ZrO2: 1%~5%; B2O3: 0.5%~8%; P2O5: 0.5%~5%; TiO2: 0%~3%; and one or more of SnO2, NaCl, Sb2O3 in a total amount of 0.1% to 2%; Among them, 0.7≤(Al2O3+Na2O) / SiO2≤1.2, 13%≤Li2O+Na2O≤30%, 1.5%≤ZrO2+P2O5+TiO2≤8%.

2. A glass-ceramic, characterized in that: In terms of molar percentage, the microcrystalline glass comprises the following components: SiO2: 40%~60%; Al2O3: 10%~22%; Na2O: 12%~25%; Li2O: 1%~7%; K2O: 0%~1%; MgO: 0.5~4%; ZrO2: 1%~3%; B2O3: 0.5%~5%; CaO: 0%~4%; P2O5: 0.5%~5%; TiO2: 0~2%; and one or more of SnO2, NaCl, Sb2O3 in a total amount of 0.1% to 2%; Among them, 0.7≤(Al2O3+Na2O) / SiO2≤1.2, 13%≤Li2O+Na2O+K2O≤30%, 1.5%≤ZrO2+P2O5+TiO2≤8%, 0.5%≤CaO+MgO+K2O≤8%.

3. The glass-ceramic according to claim 1 or 2, characterized in that: The crystal phase of the microcrystalline glass includes one or more of sodium nepheline, nepheline solid solution, triclinic nepheline, zirconium oxide, sodium phosphate, sodium silicate and beta quartz solid solution.

4. The glass-ceramic according to claim 1 or 2, characterized in that: The total crystallinity of the microcrystalline glass is above 20% and below 80%.

5. The glass-ceramic according to claim 3, characterized in that: The DSC curve of the base glass corresponding to the microcrystalline glass has a single crystallization peak or a double crystallization peak, and the intensity of the weak peak in the double crystallization peak is 5% to 80% of the strong peak.

6. The glass-ceramic according to claim 5, characterized in that: The microcrystalline glass phase with the weak peak in front in the double crystallization peak is mainly composed of triclinic nepheline, and the microcrystalline glass phase with the strong peak in front is mainly composed of sodium nepheline.

7. The glass-ceramics according to claim 1 or 2, characterized in that: The average size of crystals in the microcrystalline glass is greater than 5 nm and less than or equal to 60 nm.

8. The glass-ceramics according to claim 1 or 2, characterized in that: At a thickness of 0.7 mm, the transmittance of the microcrystalline glass at a wavelength of 400 to 750 nm is greater than 89.0%.

9. A method for preparing the glass-ceramics according to claim 1 or 2, characterized in that: include: Weigh the components according to the proportion, mix, melt and shape the components to obtain the basic glass; wherein the melting temperature is 1450-1700°C; The basic glass is subjected to a first heat treatment and a second heat treatment in sequence to obtain the microcrystalline glass; the first heat treatment temperature is 350-600°C, and the second heat treatment temperature is 540-1100°C.

10. An electronic device, characterized in that: The invention comprises: a frame and glass arranged at an opening of the frame, wherein the material of the glass is the microcrystalline glass according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • High-crystallinity sodium nepheline transparent glass-ceramics and preparation method thereof

    CN109608047A

  • Glass ceramic, glass ceramic product and manufacturing method thereof

    CN116023034A

  • Method for regulating crystallization of microcrystalline glass and product thereof

    CN116444140A